The Assessment of the Criteria of Social Infrastructure within the Scope of Women-Friendly City Approach: The Example of Çiğli - Mercan Efe Güney; Beste Tuncay; Sıdal Tanrıverdi; Nurseli Şanlı; Hacer Akbudak; Filiz Ay (Iconarp International Journal of Architecture and Planning, 2022)
The ability to reproduce, liberate and socialize individuals in a city directly depends on the existence of social infrastructure areas and the usability of these areas. Therefore, social infrastructure areas should be open to the use of all citizens and should meet the needs and demands of all citizens. This requirement depends on the consideration of the user profile as well as the conditions in the legislation. In other words, social infrastructure areas should, on the one hand, meet the criteria of distance and size per person as defined in the legislation, and on the other hand, they should be designed with the user profile in mind. Providing these two features means that the social infrastructure areas comply with the criteria of a woman-friendly city with an urban planning approach for everyone. Planning social infrastructure areas according to women-friendly city criteria is one of the basic requirements for the realization of gender equality. Therefore, city planning, as a science and profession, should produce a process and language that considers gender equality within the scope of social reinforcement areas. As long as this cannot be done, social equipment areas will be problem areas that only exist in the city. This article has been prepared in order to develop suggestions for examining and evaluating social infrastructure areas within the scope of the woman-friendly urban planning approach of city planning and producing solutions to the identified problems. The article presents a model that is open to development by proposing new principles on the approach of the women-friendly city to social infrastructure areas in terms of examination, evaluation, and solution proposition. The article aims to contribute to the increase of women-friendly cities and gender equality studies while revealing which data and how social infrastructure areas should be examined according to the legislation and women-friendly city criteria.